Seroprevalence of measles antibodies in women born between 1985 and 1999 in metropolitan city in India: a cross-sectional study - Rujuta Hadaye; Pradnya D Chandanshive; Nishat Khan (BMJ Public Health)
Introduction The Universal Immunisation Programme of India recommends first dose of measles vaccine in children at 9 months as the infant is protected by the maternal antibodies till then, and the vaccine provides optimal protection. However, during the recent outbreaks in 2023, in Mumbai, India, 31% of the measles cases reported till March end were infants below 9 months of age. The study was undertaken in view of increased vulnerability of infants below 9 months of age which might possibly indicate insufficient maternal antibodies against measles.Aim and objectives To estimate the seroprevalence of measles antibodies among women born between 1985 and 1999, most likely unvaccinated or vaccinated with a single dose of measles vaccine as per vaccination schedule prevalent then.Methodology This is a cross-sectional study conducted during November 2023 to January 2024 in the M/East municipal ward of the metropolitan city of Mumbai, Maharashtra, India. A total of 214 women were enrolled and interviewed at the nearest health centre. Their blood samples were analysed for IgG antibodies against measles using ELISA. Statistical analysis was performed to find the seroprevalence and its association with various factors using SPSS V.28.Results A total of 214 participants with a mean age of 30.9 years (SD= ±4.5) were included in the study. The mean measles IgG antibody titre among the participants was found to be 1.23 (SD= ±0.32) IU/mL, with as much as 37 (17.3%) women being seronegative for measles IgG. Thirty-four (15.9%) women had borderline (unequivocal) titre, and only 143 (66.8%) of the mothers had adequate antibodies to protect their infants.Conclusion Almost one third of women exhibited insufficient antibodies to protect their babies. It was observed that those who have received measles vaccine in their childhood were more likely to have a positive measles antibody titre and immunity against the disease.